Case Studies in Applying Design Thinking to Course Design in Computer Engineering - Rover, Diane T.; Duwe, Henry; Jones, Phillip H.; Fila, Nicholas D.; Mina, Mani (Proceedings - Frontiers in Education Conference, 2023)
This Innovative Practice Full Paper describes case studies from an instructional design process based on design thinking, illustrating tools used during stages of design. Instructional teams investigated the potential relevance of design thinking in engineering course design in electrical and computer engineering. Two teams of educators used a design thinking process in the redesign of two computer engineering courses, one in embedded systems and one in computer organization and architecture. The process of applying design thinking methods and tools was led by a facilitator with expertise in design thinking and electrical and computer engineering. The process leveraged specific tools and collaboration. This paper presents examples from each course, focusing on the design thinking tools used by the instructors and team members, highlighting what design thinking looks like when applied in this setting, and giving specific examples. The purpose is to suggest strategies and provide information and guidance for educators to use tools in their own course design efforts.